Tissue engineering approach to the creation of grafting material for rhinoplasty: clinical case reports - Vladimir Karpiuk; Irina Gilevich; Marina Perova; Olga Ponkina (Exploration of BioMat-X)
The use of autologous cartilage and bone grafts remains the gold standard in augmentation rhinoplasty performed to reconstruct of the nasal dorsum. Meanwhile, limited number of available sources, donor site morbidity, and unpredictable graft resorption represent significant disadvantages of autografting. The aim of this study is to test combination of autologous stromal vascular fraction (SVF) and commercially available bone substitutes (BSs) as new tissue-engineered grafting material (GM) for rhinoplasty. A series of consecutive cases includes four adult patients who underwent rhinoplasty to correct saddle nose deformity (SND) using the new graft technique. SVF was isolated from liposuction aspirate using standard methodology of enzymatic digestion. Two types of BSs were combined with SVF: Bio-Oss granules to create a moldable graft (M-graft), and block-shaped BoneMedik-S to create rigid grafts (R-grafts). The moderate SND was treated using an M-graft. In case of major or complex SND, the nasal dorsum was reconstructed with dorso-columellar L-shaped framework made of R-grafts. The results were evaluated over a period of 6 months to 3 years postoperatively using photogrammetry and FACE-Q appearance appraisal scales. Computerised tomography (CT) scanning of the reconstructed nose and histological analysis of grafted material were also carried out. No complications were observed. The photograms show the restoration of the correct contour of the nose. FACE-Q appraisal scale scores increased significantly, including satisfaction with nose appearance, psychological well-being, and social function. In CT evaluation, there was no substantial resorption or warping of the grafts. Histological findings show osteogenic remodeling of the grafted material. Thus, combining autologous SVF with BSs is a promising strategy for developing rhinoplasty GM.